REVITALIZING HARVEST THEOLOGY FOR AN EFFECTIVE MISSION TODAY - Frans M. H. Silalahi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
There is a decline in the population of Christians in the world from 2010 to 2020, and the primary cause is the slowing down of mission and evangelization efforts. Christians no longer see the urgent need of reaping the harvest of souls. Therefore, there is a need for Harvest Theology based on a solid biblical foundation to revitalize today’s mission. This paper uses exploratory and explanatory research methods to come up with a conclusion that churches need to develop Harvest Theology that creates effective strategies as well as focuses resources to reach receptive people; especially among the unreached people group. Harvest Theology is a counter to search theology that emphasizes finding the lost and multiplication of churches. Harvest Theology is very important to be revitalized because of the declining percentage of Christians in the period 2010 to 2020. Through exploratory and explanatory research methods, the author tries to convince readers that Harvest Theology is based on a solid biblical foundation and is vital to revitalizing today's mission. In revitalizing Harvest Theology, we need to develop mission strategies that focus on receptive people, which will give a great harvest in today's mission.